DISAIN VISUAL DALAM PEMASARAN OTOMOTIF Studi Komunikasi Bisnis - Prasetyo Adinugroho (Media Bahasa, Sastra, dan Budaya Wahana, 2018)
AbstractThis study aims to reveal, explain and analyze the visual design in automotive marketing and the desired image of the visual design. In addition, this study also describes and analyzes the layout, typography, and color visual design that illustrates excellence cars sold. The theory used in this research is the theory of imaging of the image Liliweri present (current image) is the image of an image to get a good impression gained from other people about the company or other matters relating to the products. This refers to the image to be conveyed to the public on the visual design has been designed by the company Mercedes Benz, Hyundai, and Mazda. This type of research is qualitative with the object of his research is the visual design of the company Mercedes Benz, Hyundai and Mazda. The informants in this study is Rahmadina Anggraini as Manager of Marketing PT. Mercedes Benz Indonesia, then Molly Munir as Manager of Marketing PT. Hyundai Mobil Indonesia and also Astrid Ariani Wijaya as Marketing Manager PT. Mazda Motor Indonesia. The results showed that in the manufacture of that product brochures displayed can give the image that we want to get positive results in the community. So we want to show the products in accordance with the character of the product, the product on the layout to be adjusted by the background color of the product with the product along with the tagline, headlines and company logo. However, it must include all the elements of aesthetics require that the products shown can be attractive for customers to buy its products.Keywords : Visual Design and Marketing Automotive